2012
DOI: 10.1016/j.apenergy.2012.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of biofuel as an alternative fuel for diesel engines

Abstract: International audienceThe growth of energy demand and limited fossil fuel resources lead to renewable energy development such as vegetable oils and animal fats or their derivatives. In the present work, the valuation of waste fish fat by the pyrolysis technique with the presence of catalyst to produce biofuel for diesel engines. As a result, fuel undergoes good combustion and hence there is a significant improvement in performance and reduction in emissions. The brake thermal efficiency of neat biofuel is 32.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…At lower load, BTE with blended diesel (diesel with de‐inking sludge pyrolysis oil) was found 4% higher than diesel, but it is closer at full loads . The higher BTE of fish pyrolysis oil on a single‐cylinder air‐cooled diesel engine was more reported than diesel (32.4% with fish pyrolysis oil, 29.98% with diesel) because of higher oxygen concentration with fish oil . It was found that BTE was increased with pine oil injection at full loads with better evaporation and atomization as the pine oil was dispersed with preheated air at 150 °C in an inlet manifold .…”
Section: Utilization Of Waste Plastic Oil With Diesel Enginementioning
confidence: 98%
“…At lower load, BTE with blended diesel (diesel with de‐inking sludge pyrolysis oil) was found 4% higher than diesel, but it is closer at full loads . The higher BTE of fish pyrolysis oil on a single‐cylinder air‐cooled diesel engine was more reported than diesel (32.4% with fish pyrolysis oil, 29.98% with diesel) because of higher oxygen concentration with fish oil . It was found that BTE was increased with pine oil injection at full loads with better evaporation and atomization as the pine oil was dispersed with preheated air at 150 °C in an inlet manifold .…”
Section: Utilization Of Waste Plastic Oil With Diesel Enginementioning
confidence: 98%
“…8). Este resultado puede ser atribuido al aumento de la cantidad de oxígeno disponible para la combustión con la adición de OCR al diésel, lo cual favoreció el proceso de oxidación en la cámara de combustión y redujo las emisiones de CO en los gases de escape (Yadav et al, 2016;Chuah et al, 2015;Varuvel et al, 2012).Resultados similares a los reportados por Cheikh et al (2016), quienes establecieron que, a altas velocidades y cargas máximas, se generó una disminución de 8,2% en las emisiones de CO de mezclas de biodiésel de cocina usado/ diésel al 50% vol., en comparación con el combustible diésel de referencia, la cual atribuyen al aumento en la concentración de oxígeno en el combustible y la temperatura de combustión en la cámara. Así mismo, Abedin et al (2016) reportan que el incremento en el contenido de oxígeno en mezclas de biodiésel de palma/ diésel y b de laurel de Alejandría (20 %vol.)…”
Section: Gases De Combustiónunclassified
“…Random error can only be predictable statistically and cannot be predicted in advance. Its presence can be detected only when the same parameter is measured again and again under the similar conditions and with the proper attention (Varuvel et al, 2012). The magnitude of the error can be found by the principle of root sum-square method.…”
Section: Analysis Of Uncertaintymentioning
confidence: 99%